Recent Advances in the Synthesis of Pyrazole Derivatives: A Review - Issam Ameziane El Hassani; Khouloud Rouzi; Hamza Assila; Khalid Karrouchi; M’hammed Ansar (Reactions, 2023)
Pyrazole, characterized by a five-membered heterocyclic structure featuring two neighboring nitrogen atoms, serves as a core element. Pyrazoles hold a privileged status as versatile frameworks in various sectors of the chemical industry, including medicine and agriculture. Previous reviews have extensively highlighted the significance of pyrazoles and their diverse biological activities, encompassing roles such as antituberculosis, antimicrobial, antifungal, anti-inflammatory, anticancer, and antidiabetic agents. Consequently, they have garnered substantial interest from researchers. The aim of this review is to offer a comprehensive overview of the published research related to the synthesis of pyrazole derivatives, encompassing a discussion of diverse methods for accessing the pyrazole moiety. These methods span from utilizing transition-metal catalysts and photoredox reactions to employing one-pot multicomponent processes, novel reactants, and innovative reaction types. It encompasses studies conducted by numerous scientists worldwide, showcasing collective efforts in advancing the methodologies and applications of pyrazole derivatives.